Analisis Program Bedug Sedekah Subuh terhadap Perubahan Pola Berderma Digital (Studi Kasus LAZ Dompet Sejuta Harapan) - Eka Novita Sari (Institut Agama Islam Negeri Ponorogo, 2026)
This study examines the adaptation of the Bedug Sedekah Subuh Program at LAZ Dompet Sejuta Harapan to the shift in digital donation patterns. Initially relying on traditional methods such as direct collection through bedug-shaped piggy banks, the program now faces challenges to remain relevant in the digital era amid the rise of online donation platforms. Employing a qualitative approach with a case study method, data were gathered through interviews, observations, and document analysis. The findings reveal that LAZ Dompet Sejuta Harapan has adopted digital strategies, including social media promotion and QRIS integration into the bedug, but encounters obstacles such as low digital literacy among donors, particularly in rural areas, and trust issues regarding digital transaction security. Nevertheless, this adaptation offers opportunities to reach a wider donor base and enhance operational efficiency. The study suggests improving digital literacy, ensuring transparency in fund management, and collaborating with digital platforms to optimize the program.